O uso da calculadora HP-12C nas operações de matemática financeira comercial com ênfase na análise de investimento - Falcão Neto, Antônio (2011)
The Financial Mathematics treated in this issue presents two points of view, the methodological theoretical and the use of the machine technology. Its purpose is to contribute with the use of the calculator HP 12C in the elementary, secondary and higher education, providing for the students more interest and motivation to learn subject like this in their professional lives. So, we elaborate a tutorial with elementary operations about the structure of Financial Mathematics that help to solve practice situations and obtain the discernment between buying the spot or forward. The adequate use of this tutorial, help to solve practice situations and understand how to work the Financial Mathematics and allowing to foresee the results of investments in business. We also treat in this tutorial the amortization of financing systems currently in use, simple and compound capitalization, cash flow, net present value, internal rate of return and pension fund.